Moderating or mediating effects of family characteristics on socioeconomic inequalities in child health in high-income countries: a scoping review - Hoffmann, Stephanie; Sander, Lydia; Wachtler, Benjamin; Blume, Miriam; Schneider, Sven; Herke, Max; Pischke, Claudia Ruth; Matos Fialho, Paula; Schüttig, Wiebke; Tallarek, Marie; Lampert, Thomas; Spallek, Jacob (BMC public health, 2022)
Child, Family, Health, Health status disparities, Infant, Socioeconomic factors, Socioeconomic health inequalities